2019
DOI: 10.1108/cms-05-2018-0517
|View full text |Cite
|
Sign up to set email alerts
|

Can ethical leadership hinder sales performance? A limited resource perspective of job embeddedness

Abstract: Purpose The purpose of this study is to borrow from a limited resource view of job embeddedness to argue that ethical leadership can hurt salespeople’s growth of sales performance by a latent growth model. Design/methodology/approach This work surveyed 825 salespeople in Greater China at three points over six months to test the latent growth model. Findings The findings reveal that as salespeople perceive more ethical leadership at the initial point, they may show more increases in job embeddedness behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
0
13
0
1
Order By: Relevance
“…The results suggest that EL develops a conducive environment and establish transparent and inclusive links among employees and key stakeholders (e.g., community and organization) to ensure that employees feel relevant and valued, thereby paving the way for pro-leaders and organization-centric sentiments. This finding makes sense, given that employee assessment and response to leaders and organizations depend on the perceived emotional, financial, and ethical support ( Lee and Huang, 2019 ). In line with earlier assertions (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that EL develops a conducive environment and establish transparent and inclusive links among employees and key stakeholders (e.g., community and organization) to ensure that employees feel relevant and valued, thereby paving the way for pro-leaders and organization-centric sentiments. This finding makes sense, given that employee assessment and response to leaders and organizations depend on the perceived emotional, financial, and ethical support ( Lee and Huang, 2019 ). In line with earlier assertions (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Such practices nurture identity, motivation, JE, leader-member exchange, psychological contract, and organizational engagement ( Chen and Hou, 2016 ; Xu et al, 2016 ; Hoch et al, 2018 ; Rodriguez, 2018 ; Ahmad et al, 2019 ). Several preceding studies have validated positive links between EL and JE in different forms ( Lee and Huang, 2019 ). In another study, Al-Ghazali (2020) built an OST-based model to examine the nexus between transformational leaders, career success, and CS using data from nurses working in the government hospitals in Saudi Arabia.…”
Section: Outcomes Of Ethical Leadership: a Theoretical Perspectivementioning
confidence: 90%
“…We collected samples of CEOs and SETs of medium-sized technology farms in Taiwan for PGM analysis over three separate time periods with an interval of three months. Each time period is separated by three months to satisfy PGM statistical analysis [43][44][45].…”
Section: Samplementioning
confidence: 99%
“…Ethical leadership refers to decent behaviors shown by leaders in their interpersonal interactions, and it will influence employees through mutual communication, management practice and decision-making (Brown et al , 2005). Although there are a few researchers find the dark side of ethical leadership (Lee and Huang, 2019a), most empirical studies showed that ethical leadership, as a positive leadership style, can reduce negative employee attitudes/behaviors such as burn-out and workplace deviance (Mo and Shi, 2017), and bring positive outcomes relating both to individuals and organizations such as employee performance and well-being (Lee and Huang, 2019b), voice and psychological ownership (Avey et al , 2012), organizational citizenship behaviors (Abdulkareem and Tarik, 2018), knowledge sharing behaviors (Lei and Ba, 2018) and organizational knowledge sharing climate (Lei et al , 2019).…”
Section: Theory and Hypothesismentioning
confidence: 99%